(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The economic misery index is one of the indicators that are used to determine the extent of the bad or quality of the overall economic performance and the extent of the economic well-being of the citizens of the country. Iraq due to the economic conditions that the country is exposed to, which was reflected in the time periods included in the study of the misery index in the Iraqi economy. One of the most important findings of the research is that the Iraqi economy went through two important stages during the study period extending from 1990 to 2018 in measuring the economic misery index, as it witnessed fluctuation in these stages between rise and fall due to the economic conditions that the Iraqi economy went through from siege and war. And the state is able to reduce the causes of this problem by working to reduce the rates of economic misery by creating a clear economic vision for the advancement of the Iraqi economy to achieve the well-being of all members of Iraqi society and improve their quality of life.